Anaesthesia Comparison of the electrocardiographic findings, heart rates, cloacal temperatures, respiratory rates, and anaesthetic effects of medetomidineketamine and detomidine-ketamine combination in the buzzards (Buteo buteo) - Yaygingul, R; Bozkan, Z; Bulut, O; Yldirim, EK; Sarierler, M (Journal of the Hellenic Veterinary Medical Society, 2023)
The aim of the present study was to compare the electrocardiogram findings, heart rate, cloacal temperature, respiratory rate, and anaesthetic effects of medetomidine- ketamine or detomidine-ketamine anaesthetics in buzzards. Fourteen buzzards of unknown sex and age and weighing a mean ± standart deviation (SD) of 789.29 ± 82.97 g each were used for the study. The buzzards were randomly assigned to two groups: MK group (0.1 mg kg-1 medetomidine and 10 mg/kg ketamine intramuscularly) and group DK (0.3 mg/kg detomidine and 10 mg/kg ketamine intramuscularly). Heart rates (HR), respiratory rates (fR), and cloacal temperatures (CT) were recorded before administration of any drug (0) and then 5 and 10 minutes after medetomidine and 5, 10, 15, 30, 45, 60 minutes after ketamine. At this point, Atipamezol (0.5 mg/kg) was administered and measurement recorded at 5, 10 and 15 minutes. Serum electrolyte, blood gases and electrocardiograms were measured before and during anesthesia. Distribution and fitness of the data were evaluated by the Shapiro-Wilks test. Statistical tests were performed via two-way variance analysis in repeated measures, and multiple comparisons were corrected with the post-hoc Generalized Linear Model (GLM). Differences were considered to be statistically significant if p < 0.05. Onset of anesthesia time was 4.1 ± 2.3 and 3.9 ± 1.3 minutes (mean ± standard deviation) in groups MK and DK, respectivel. Reflexes (righting reflex, toe pinch reflex, feather plucking reflex, palpebral reflex) disappeared studied in both groups during anesthesia. HR, fR, and CT were significantly decreased in both groups (p < 0.001). Blood gases values were significantly increases in pCO2 and HCO3 and decreased pH and pO2 in both groups (p < 0.05). Conclusions and clinical relevance, It was concluded that both anesthesia protocols are effective approaches for minor and major operations in buzzards.